Efektivitas Kebijakan Penghimpunan Dana Zakat Infaq Dan Sodaqoh (ZIS) Dengan Menggunakan Payroll System - Aminah, Siti; Maulida, Atika Zahra (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This study aims to analyze the effectiveness of the ZIS fund collection policy using the payroll system for civil servants by BAZNAS Banjarmasin City as the fund collector and manager. The type of research used is empirical legal research with a combination approach (mix methods). The population of this study is 4,562 people. The research sample is 4,442 people with purposive sampling technique. Data analysis uses interactive analysis techniques and descriptive statistics. The results of the study are known from the collection of the ZIS payroll system for Banjarmasin City civil servants by BAZNAS Banjarmasin City in the process of the payroll system is carried out through a 2.5% salary deduction for muzakki civil servants in groups III and IV. Then deductions of Rp. 5,000 and Rp. 10,000 for civil servants of groups I and II by the treasurer in each work unit. This policy is considered quite effective in collecting ZIS funds with the fulfillment of the indicators of substance, structure and legal culture. However, due to the policy being applied without coercion and is not required to all civil servants, the potential for ZIS payroll system funds for Banjarmasin City civil servants in 2023 is not in line with its realization. The contribution of this research is the evaluation of the implementation of the ZIS collection policy using the payroll system. In addition, the results of this study can be a model for implementation in other regions, especially in building a more structured, transparent, and legal-based ZIS collection system.